Comparative analysis of the CLOC/Vía Campesina peasant agroecology schools in Latin America and the Caribbean - St Fleur, Magorie; Rosset, Peter Michael [UNESP]; Elizondo, Cecilia; Val, Valentin (Univ Federal Norte Tocantins-ufnt, 2024)
This article provides a comparative analysis of the schools or peasant universities of the Latin American Coordination of Rural Organizations (CLOC) and La Via Campesina (LVC) in Latin America and the Caribbean, and of the Peasant Movement of Papaye (MPP) in Haiti, with emphasis on the Latin American Agroecological Institutes (IALA), which exist to offer agroecological, political and organizational training especially to peasant, indigenous and Afro-descendant youth in the region. The objective is to systematize and compare the training programs of the CLOC/VC schools and the MPP school, to extract useful lessons that can support the advancement of both, as well as provide important elements for the promotion of agroecology and social transformation in the region, in order to better understand the educational practices and pedagogical approaches used in different contexts. And also, to explore in depth, the structure, functioning, impact and current challenges of the CLOC/VC schools in the region. It highlights the importance of these institutions in the training of women, men and young peasant leaders, and in the promotion of agroecology and food sovereignty in the region. The study includes a literature review, a detailed analysis of the schools in different countries, with interviews with members of the coordinations, and focuses on the organizational structure, educational programs and social impact. Differences in infrastructure and resources, and similarities in pedagogical approaches are revealed. The discussion focuses on the implications of these findings for strengthening peasant education and the massification and territorialization of peasant agroecology, and strategies are proposed to improve the quality and sustainability of the schools. The importance of supporting CLOC/VC and MPP schools to ensure their impact on rural communities in the region is emphasized.
Keywords: : IALA; CLOC; Latin America; Haiti; peasant schools; agroecology